The red thread : a novel in three incarnations - Townley, Rod (Atheneum Books for Young Readers, 2007)
Bothered by insomnia, nightmares, and claustrophobia, sixteen-year-old Dana sees a therapist who hypnotizes her into remembering past lives, involving her in an age-old mystery and causing her to question what kind of person she is.